Use and costs of inhaled nitric oxide and inhaled epoprostenol in adult critically ill patients: A quality improvement project. (2nd August 2019) - Davis, Stephanie L; Crow, Jessica R; Fan, John R; Mattare, Katie; Whitman, Glenn; Brower, Roy G; Rowden, Annette; Pustavoitau, Aliaksei
Abstract: Purpose: Inhaled epoprostenol and inhaled nitric oxide are pulmonary vasodilators commonly used in the management of acute respiratory distress syndrome and right ventricular failure; however, they have vastly different cost profiles. The purpose of the project was to transition from nitric oxide to epoprostenol as the inhaled pulmonary vasodilator (IPV) of choice in adult critically ill patients and evaluate the effect of the transition on associated usage and costs. Methods: A single-center, prospective, before and after quality improvement project including adult patients receiving inhaled nitric oxide, inhaled epoprostenol, or both was conducted in 7 adult intensive care units, operating rooms, and postanesthesia care units of a tertiary care academic medical center. The total number of patients, hours of therapy, and costs for each agent were compared between stages of protocol implementation and annually. Results: Seven hundred twenty-nine patients received inhaled nitric oxide, inhaled epoprostenol, or both during the study period. The monthly inhaled nitric oxide use in number of patients, hours, and cost decreased during all stages of the project ( p < 0.01). The monthly inhaled epoprostenol use in number of patients, hours, and cost increased during all stages ( p < 0.01). Overall, total IPV use increased during the study. However, despite this increase in usage, there was a 47% reduction in total IPV cost. Conclusion: Implementation of a staged protocol to introduce and expand inhaled epoprostenol use in adult critically ill patients resulted in decreased use and cost of inhaled nitric oxide. The total cost of all IPV was decreased by 47% despite increased IPV use.